Connected Gaming: An Inclusive Perspective for Serious Gaming - Yasmin Kafai (Serious Games Society, 2017)
Serious games should focus on connected gaming, which is combining the instructionist approach on having students play educational games for learning with the constructionist approach on having students make their own games for learning. Constructionist activities have always been part of the larger gaming ecology but have traditionally received far less attention than their instructionist counterparts. Future developments in serious gaming ought to promote this more inclusive perspective to better realize the full potential of gaming as a means for learning and for connecting children to technology and to each other. This potential for more meaningful connectivity can also address the persistent access and diversity issues long facing gaming cultures.